Early Quaternary sedimentary processes and palaeoenvironments in the central North Sea. (11th October 2016) - Lamb, Rachel M.; Huuse, Mads; Stewart, Margaret
ABSTRACT: A number of elongate trough‐like features are observed in the early Quaternary succession of the central North Sea basin. A definitive model of formation for the features remains unclear but the troughs may aid in our understanding of the depositional environment of the early Quaternary. In total, 380 troughs were mapped over 11 000 km 2 using continuous 3D seismic data and analysed in conjunction with well log data and understanding of the probable palaeogeographical context. The troughs were formed in a marine setting on the slope of a large clinoform set during a period of rapid progradation. The geometry and infill of the troughs, as well as the marine setting, strongly support a model of repeated density‐driven downslope flows which excavate and then infill the troughs perpendicular to the strike of the slope. A subset of the troughs are observed to form parallel to the strike in such a way that cannot be easily explained by downslope processes alone. A number of possible models are considered for the formation of these along‐slope troughs; here we conclude that the most likely scenario involves modification of the downslope flows by currents which divert the features along‐slope while maintaining the erosive nature of the flow.